Effect of Hydrodynamic Cavitation Assistance on Different Stages of Coal Flotation - Hua Han (Minerals, 2020)
In this study, the effect of hydrodynamic cavitation (HC) on the conditioning stage (HCCS), separation stage (HCSS), and whole stage (HCWS) of coal flotation was investigated by flotation tests, laser granulometry, and contact angle measurements. The flotation results indicate that compared to conventional flotation, all HC-assisted flotation methods can improve concentrate combustible recovery and flotation constant rate. HCCS and HCSS show similar levels of improvement, while HCWS has a better flotation efficiency. The screening tests demonstrate that HC has the advantage of being able to liberate coarse coal particles (+0.25 mm) prior to being combined with gangues. On one hand, HC promotes the dispersion of both particles and agents, while longer cavitation time in HCCS does not lead to better flotation performance. On the other hand, enhancement of the adsorption of the collector on the surface of coal particles in HCCS is confirmed by flotation concentrate contact angle tests. However, HCSS leads to a decrease in concentrate hydrophobicity, compared to conventional flotation. The micro-nanobubbles generated by HC play an important role in improving flotation performance. HCWS offers the advantages of both HCCS and HCSS, and the cooperated mechanism of different HC modes enhances the recovery of coal particles in flotation.